Hydrometallurgical processing of nickel lateritic ores - Stopić, Srećko R.; Friedrich, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Nickel production is a very important activity for the European Union because nickel is a unique constituent of stainless steel. Europe has lateritic (oxidic) ore deposits along a very well-known belt starting from the Alps and ending to the Himalayas. The lateritic belt passes through western Balkans and Greece and continues through Turkey to Asia. The known lateritic deposits in Serbia are located in three different areas called: Zapadna Morava (Rudjinci, Veluce, Ba), Sumadija (Lipovac, Kolarevici, Bucje) and Mokra Gora, which have many natural resources such as forests, rivers, etc. Therefore, it is  very important to understand and show hydrometallurgical treatments of lateritic ores via mining and metallurgy in different parts of the world. In this paper, several exploitation scenarios for hydrometallurgical treatment and benefication of lateritic ores will be shown: Direct Nickel Process, Ravensthorpe and Murrin Murrin in Australia and Meta Cobalt Nickel in Turkey.
Keywords: Nickel; cobalt; lateritic ore; hydrometallurgy; autoclave